PERAN LIKUIDITAS, MODAL KERJA, DAN KINERJA DALAM MENENTUKAN NILAI PERUSAHAAN: KASUS PT. ACE HARDWARE INDONESIA, TBK (2011-2020) - Pangaribuan, Hasudungan (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
This research aims to determine the influence of Liquidity (CR), Working Capital (WCT) and Company Performance (ROE) on the Company Value of PT. Ace Hardware Indonesia Tbk is listed on the Indonesia Stock Exchange for the 2011-2020 period, either partially or simultaneously. The population used in this research is a retail company for household needs and lifestyle, namely PT. Ace Hardware Indonesia 2011-2020. Data analysis uses normality tests, multicollinearity, autocorrelation, multiple linear regression, determination, F test and T test. Based on the results of the research that has been carried out, a conclusion can be made, namely that the Liquidity Variable (Current Ratio) is positive and significant to Company Value. The Working Capital Variable (Working Capital Turnover) has a positive and significant effect on Company Value. The Company Performance Variable (Return On Equity) does not have a significant effect on Company Value. Simultaneously, Liquidity (Current Ratio), Working Capital (Working Capital Turnover) and Company Performance (Return On Equity) do not have a significant effect on Company Value.